2019
DOI: 10.1155/2019/9360542
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Carbon Monoxide-Induced Delayed Neurological Sequelae Successfully Treated with Hyperbaric Oxygen Therapy, N-Acetylcysteine, and Glucocorticoids: Clinical and Neuroimaging Follow-Up

Abstract: Carbon monoxide (CO) poisoning is a leading cause of intentional and unintentional poisoning worldwide, associated with mortality and severe morbidity. Some survivors of CO poisoning develop, after a lucid interval, a potentially permanent encephalopathy in the form of cognitive impairment and movement disorders, such as Parkinsonism. One of the most frequent neuroimaging findings is a cerebral white matter damage, but so far its precise cause and specific therapy are still debated. We here report the case of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…Current literature on DNS treated with delayed HBOT plus ROS-scavenger drugs is scanty. One such report was by Spina et al, who reported the clinical-radiological follow-up of a DNS case treated with HBOT, N-Acetylcysteine and glucocorticoids, who had a progressive and sustained clinical and radiological improvement [6]. This case is strikingly similar to ours, as were the treatment modalities, including late HBOT.…”
supporting
confidence: 77%
“…Current literature on DNS treated with delayed HBOT plus ROS-scavenger drugs is scanty. One such report was by Spina et al, who reported the clinical-radiological follow-up of a DNS case treated with HBOT, N-Acetylcysteine and glucocorticoids, who had a progressive and sustained clinical and radiological improvement [6]. This case is strikingly similar to ours, as were the treatment modalities, including late HBOT.…”
supporting
confidence: 77%
“…23,24 We speculate that if CO can deteriorate OPCs, 3 the delayed neurological sequelae-associated effects of CO can be exaggerated or accelerated in the OPC-related GBM. 25,26 The limitations include the characteristics of this study, methodology, included patients, behavioral differences, and migration issues. As this is an observational study, our result shows a preliminary example of the association of the air pollutant and not address the causality of the phenomenon.…”
Section: Discussionmentioning
confidence: 98%
“…it is still uncertain whether the air pollutant affected the nonbiological factors, the baseline patient condition, other organs such as heart, other factor/cells in the bloodstream, cancer‐origin‐related cell (such as oligodendrocyte progenitor cells [OPC]), the tumor cell itself, the necrotic portion of the disease, or its surrounding cells 23,24 . We speculate that if CO can deteriorate OPCs, 3 the delayed neurological sequelae‐associated effects of CO can be exaggerated or accelerated in the OPC‐related GBM 25,26 …”
Section: Discussionmentioning
confidence: 99%
“…There is no consensus regarding the treatment of DNS. Several studies have found that HBOT alone or combined with steroids, N-butylphthalide, or N-acetylcysteine seemed to achieve better neurological recovery[ 20 , 21 ]. The anti-inflammatory and anti-oxidative nature of these medications are capable of attaining similar results to those of ILIB therapy[ 8 ].…”
Section: Discussionmentioning
confidence: 99%